2005
DOI: 10.1038/modpathol.3800232
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer–testis antigens in endometrial carcinomas using a tissue microarray

Abstract: Cancer-testis (CT) antigens are expressed in a variety of malignant tumors, but in normal adult tissue, they are only expressed in testicular germ cells. Owing to this tumor-associated expression pattern, these antigens are of major interest as potential targets for immunotherapy and possibly for diagnostic purposes. This study was performed to analyze the expression of four CT antigens, NY-ESO-1, MAGE-A3, MAGE-A4, and CT7/MAGE-C1, in endometrial carcinoma using immunohistochemistry, and to correlate expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
0
20
2
Order By: Relevance
“…This finding is in contrast to results obtained by Resnick et al who observed higher incidence of expression using immunohistochemistry (5). However, our data are in concordance with another report that found only 6% of endometrial cancers expressed NY-ESO-1, and 23% expressed MAGEA4 (6). We chose to re-evaluate NY-ESO-1 expression in our cancers by conventional nonquantitative reverse transcription-PCR.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This finding is in contrast to results obtained by Resnick et al who observed higher incidence of expression using immunohistochemistry (5). However, our data are in concordance with another report that found only 6% of endometrial cancers expressed NY-ESO-1, and 23% expressed MAGEA4 (6). We chose to re-evaluate NY-ESO-1 expression in our cancers by conventional nonquantitative reverse transcription-PCR.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, PRAME was identified as a cancer biomarker based on its increased level of expression in a comparison of normal endometrium and endometrial cancer. 6 This expression in the most common histologic type of endometrial cancer deserves further investigation, including analysis of the relative levels of transcript and protein in normal and malignant uterine tissue. Recent progress in the understanding of the role of PRAME in modulating tumor progression through retinoic acid signaling further highlights the need for more study in this area (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of the majority of the CTAs is still unknown; however, some CTAs are thought to be implicated in the regulation of gene expression and others may control gametogenesis (Old, 2001;Kalejs and Erenpreisa, 2005). The CTAs are attractive targets for developing cancer-specific immunotherapy because of their highly restricted expression in normal tissues and broad expression in a wide range of tumours (Chitale et al, 2005).…”
mentioning
confidence: 99%
“…Also referred to as 'cancer-testis antigens', they are not expressed in normal tissues except the testis and placenta. In neoplastic lesions, they have been found to be expressed in 12-60% of solid malignant tumors including lung (Fischer et al 1997, Jang et al 2001, liver (Kobayashi et al 2000), endometrial (Chitale et al 2005), and genitourinary carcinomas (Hudolin et al 2006, Picard et al 2007) and cholangiocarcinomas (Tsuneyama et al 2004).…”
Section: Introductionmentioning
confidence: 99%